Sumber Otoritas Pelaksanaan Supervisi - Fathimah, Meti; Munzillah, Indiarti Muafiqoh; Zubaidah, Citra (TSAQOFAH, 2025)
Supervision in the context of education, management, and various other fields, is an important activity to ensure that the implementation of tasks, functions, and policies runs well and in accordance with the standards that have been set. The source of authority in the implementation of supervision is one of the most important aspects to pay attention to. The authority refers to the authority or legitimacy possessed by the supervising party to direct, assess, or give instructions to the supervised party. In this context, understanding the various sources of authority in the implementation of supervision can help leaders, supervisors, or parties responsible for carrying out supervision to carry out their duties more professionally and based on the principles of justice and ethics that apply.